Effect of different feed pellet on growth rate and survival levels of tilapia seeds (Oreochromis niloticus) - Muhammad Ikhsan Wamnebo; Siti Hadijah; Andi Hamdillah (Depik, 2023)
Tilapia (Oreochromis niloticus, Linnaeus, 1758) is a dominant commodity in the Indonesian freshwater fishery industry, and its growth relies on feed. Pellet are feed that is processed through a factory mechanism or human intervention, based on the cultivators’ needs. Therefore, the purpose of this study was to determine the effect of pelleted feed with varying protein content on growth and survival of tilapia (Oreochromis niloticus) fry. This was conducted from April 2022 to June 2022, in Tasiwalie Village, Suppa District, Pinrang Regency. The test animals used were tilapia aged 30 days, and feed include omega-3, Hi-Pro-vite 781, and Prima feed 500 grams each. An experimental method was employed using a Completely Randomized Design (CRD) with three treatment and replications, where treatment A, B, and C were Prima Feed (39 – 41%), Hi-Pro Vite (protein 31 – 33%), and Omega feed (protein 13 – 16%), respectively. Artificial feed was given at a dose of 5%/body weight 3 times a day. Also, water quality management was carried out by measuring temperature, dissolved oxygen, pH, and ammonia. The results showed that different feed affected protein retention with the highest average value of 43.23%, the highest average fat retention of 48.56%, absolute weight growth of 1.58 g, absolute length growth of 2.33 cm, daily specific weight growth rate of 3.75%, daily specific length growth rate of 5.56%, and feed utilization efficiency 70.60%. Furthermore, the best growth was obtained in treatment A, involving Prime Feed from 39 – 41%. This study showed that the percentage of protein had a significant effect on growth and survival of tilapia. Therefore, the feed industry is needed to formulate requirements based on tilapia fish, to increase production.Keywords:TilapiaFeedGrowthSurvival